2018
DOI: 10.1136/bmj.k5247
|View full text |Cite
|
Sign up to set email alerts
|

The end of Brazil’s More Doctors programme?

Abstract: Those in greatest need will be hit hardest

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…In the 2013–2015 period, there was a substantial expansion in smaller municipalities, and the increase in the physician-inhabitant ratio in these locations were similar to that found in larger municipalities, especially when considering only physicians practicing in the SUS. These results reflect the importance of the PMMB's recruitment component and the government incentives to expand primary care in SUS to reduce inequalities in access to healthcare, although physicians graduated in Brazil and Brazilians trained in other countries have priority in the recruitment program, Cuban physicians, recruited as part of a Brazilian government cooperation with Cuba government, were an important contingent of professionals who practiced in rural and remote areas [ 9 , 26 ]. This cooperation generated intense debate during its establishment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 2013–2015 period, there was a substantial expansion in smaller municipalities, and the increase in the physician-inhabitant ratio in these locations were similar to that found in larger municipalities, especially when considering only physicians practicing in the SUS. These results reflect the importance of the PMMB's recruitment component and the government incentives to expand primary care in SUS to reduce inequalities in access to healthcare, although physicians graduated in Brazil and Brazilians trained in other countries have priority in the recruitment program, Cuban physicians, recruited as part of a Brazilian government cooperation with Cuba government, were an important contingent of professionals who practiced in rural and remote areas [ 9 , 26 ]. This cooperation generated intense debate during its establishment.…”
Section: Discussionmentioning
confidence: 99%
“…In December 2019, the federal government created the Doctors for Brazil Program [ 27 ]. This program established a new structure to expand the hiring of physicians in underserved areas and revoked the changes in the training of specialists defined by the PMMB [ 26 ]. However, none of the new measures proposed to increase the number of physicians in underserved areas of this program have been implemented.…”
Section: Discussionmentioning
confidence: 99%
“…These declines in ESF coverage are based on published forecasts [8], whilst a range of possible declines is tested in sensitivity analyses (Additional file 1). A contracting ESF coverage as above and termination of the MMP, which could end in 2019 due to the lack of political support from the new government [21]. This scenario additionally models specific ESF coverage declines in municipalities where Mais Médicos doctors operate.A UHC scenario, where ESF coverage increases to 100% in all municipalities by 2030, reflecting SDG 3, target 3.8 [2].…”
Section: Introductionmentioning
confidence: 99%
“…A contracting ESF coverage as above and termination of the MMP, which could end in 2019 due to the lack of political support from the new government [21]. This scenario additionally models specific ESF coverage declines in municipalities where Mais Médicos doctors operate.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, several studies have shown that the PMM mainly allowed the concretization of the principle of equity, through the distribution of doctors in PHC according to the criteria of social vulnerability and of specific populations [21][22][23][24][25] . It provided the presence of doctors in areas of difficult access, of extreme poverty, far from large centers, in the outskirts of metropolitan regions, and indigenous populations, as well as riverside, quilombolas, and rural populations [21][22][23][24][25] , who were previously excluded from the system. Nevertheless, it must be considered that, initially, part of the medical corporation was in opposition to the program, mainly due to the arrival of a large number of Cuban doctors 26 , which contributed to the creation of negative perceptions of these doctors and the program [27][28][29] .…”
Section: Discussionmentioning
confidence: 99%